A Computational Bioengineering System for Thermal Functional Design of Textile Products (Journal of Fiber Bioengineering and Informatics, 2008)
Textile thermal bioengineering design involves the integration of multidisciplinaryknowledge. Utilizing computer power and popularity to realize it creates a huge potential in designingclothing with advanced functions in an effective, economical and scientific way. This paper presentsa virtual thermal bioengineering system for life-oriented design of textile products, which, by thecombination of multidisciplinary knowledge, creates a virtual space for the designer to achieve textilebioengineering design in a life-oriented way. The thermal bioengineering framework and designprinciples of thermal functional clothing are shown, the development of the computer-aid systemincluding the life-oriented design, simulation, visualization and project management, as well as theengineering database, is reported with case illustration.